Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12889-022-12590-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and mental health during the first year of the COVID-19 pandemic: a systematic review

Abstract: Introduction The Coronavirus disease-19 (COVID-19) pandemic affected countries worldwide and has changed peoples’ lives. A reduction in physical activity and increased mental health problems were observed, mainly in the first year of the COVID-19 pandemic. Thus, this systematic review aims to examine the association between physical activity and mental health during the first year of the COVID-19 pandemic. Methods In July 2021, a search was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
114
2
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 56 publications
(167 reference statements)
9
114
2
11
Order By: Relevance
“…This could be because the time for PA in PE classes is mostly less than 60 min as well as because the PE classes included less PA due to the existing obligations to wear masks and keep a distance. Regarding the stress symptoms, the positive association of well-being with PA is in line with other studies investigating the relation of mental health and PA during the first year of the pandemic [ 33 ]. Recall that, as the causality of this relationship is not clear, it can be interpreted in both ways.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This could be because the time for PA in PE classes is mostly less than 60 min as well as because the PE classes included less PA due to the existing obligations to wear masks and keep a distance. Regarding the stress symptoms, the positive association of well-being with PA is in line with other studies investigating the relation of mental health and PA during the first year of the pandemic [ 33 ]. Recall that, as the causality of this relationship is not clear, it can be interpreted in both ways.…”
Section: Discussionsupporting
confidence: 88%
“…From a psychopathological perspective, the focus was primarily on depression. Most studies showed a negative correlation between depressive symptoms and PA in children and adolescents during the first year of the pandemic [ 28 , 33 ]. Pre-pandemic data revealed mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity is well recognized as a key factor in the prevention and management of mental illness, including mental disorders, such as depression and anxiety, as well as the promotion of mental health, such as well-being [ 50 ]. Physical activity was also found to be a good and effective choice to mitigate the negative effects of the COVID-19 pandemic on mental health during the first year of the COVID-19 pandemic [ 51 ].…”
Section: Discussionmentioning
confidence: 99%